A new Cenomanian vertebrate tracksite at Tamajón (Guadalajara, Spain): Palaeoichnology and palaeoenvironmental implications. (January 2016) - Segura, Manuel; Barroso-Barcenilla, Fernando; Berrocal-Casero, Mélani; Castanera, Diego; García-Hidalgo, José F.; Santos, Vanda F.
Abstract: A new Upper Cretaceous vertebrate tracksite has been discovered at Tamajón (Iberian Ranges, Guadalajara, Spain). The track level is a relatively smooth and slightly undulating sandy ferruginous crust, corresponding to an erosive surface at the base of a small meandering channel. It is incised into the underlying planar cross-bedded sandstones of coastal bars located at the middle-upper part of the Utrillas Formation (middle-upper Cenomanian). The site shows an extraordinary concentration of vertebrate tracks, among which numerous sets of two to five isolated digit impressions ("swim tracks") and, at least, two trackways referred to crocodyliforms, and a single tridactyl footprint probably produced by a theropod dinosaur can be recognized. There are also several long traces (epichnial grooves) revealing sharp direction changes (up to 90°) which seem to be fish fin traces ( Undichna unisulca ), although crocodyliforms (tail marks) and/or fish invertebrates cannot be rejected as possible tracemakers. Some crocodyliform tracks reveal a thin raised rim, due to the displacement of the sediment by the pressure produced by the feet. Several impressions are moderately deformed by small sediment slides, only preserving their deepest part (claw marks). This is clearly indicative of a soft substrate with a high degree of plasticity and water content at the time of the track registration. Nevertheless, the sediment was hard enough to preserve manus and pes print morphologies and also possible crocodyliform tail and/or fish fin traces. Small rhizoliths can also be recognized and may belong to herbaceous wetland vegetation. The morphology of the palaeochannel, the sedimentary context and the track preservation seem to indicate that the tracks were impressed in a shallow channel located near the coast, under wet conditions and in different moments of time. This discovery represents the first occurrence of vertebrate ichnites in the Utrillas Formation, a stratigraphic unit where osteological and ichnological remains are relatively scarce, and it confirms that some crocodyliforms lived in near coast channels during the deposition of this unit.